Perinatal glucocorticoid sensitivity in the preterm newborn: molecular mechanisms, endogenous determinants, and clinical implications - Anti, Nana A. O.; Gheorghe, Ciprian P.; Deming, Douglas D.; Adeoye, Olayemi O.; Zhang, Lubo; Mata-Greenwood, Eugenia (Frontiers in Endocrinology, 2025)
Glucocorticoids are steroid hormones that regulate multiple physiological processes throughout the lifespan and play a central role in the adaptive stress response. Their biological effects are mediated by the glucocorticoid receptor, which acts through both genomic and nongenomic mechanisms to regulate transcriptional signatures and intracellular signaling pathways, respectively. These effects are tissue- and context-dependent, allowing the body to adapt to developmental and environmental changes. Glucocorticoid-mediated effects are influenced by both hormone bioavailability and tissue-specific responsiveness. Reduced glucocorticoid sensitivity has been observed in patients with severe disease or a diminished response to synthetic glucocorticoid therapies. During the perinatal period, the endogenous glucocorticoid cortisol exerts unique developmental effects on the late-gestation fetus that are essential for extrauterine life. Antenatal glucocorticoid therapy has demonstrated beneficial effects in preventing prematurity-related diseases, while postnatal glucocorticoid treatment reduces inflammation and improves oxygenation in bronchopulmonary dysplasia. However, these therapies exhibit variable responses, both in terms of their beneficial and adverse effects. Furthermore, preterm newborns are exposed to adverse intrauterine environments, including placental insufficiency and infection, which—when combined with immaturity—result in dysregulated perinatal glucocorticoid homeostasis. Intrauterine stressors can therefore alter fetal glucocorticoid sensitivity, partially explaining the variability in clinical outcomes observed among preterm newborns. These adverse conditions may also interact with genetic and physiological factors, such as gestational age and fetal sex, further amplifying glucocorticoid homeostasis dysregulation. In this review, we explore the clinical and basic science evidence on the endogenous determinants of perinatal glucocorticoid sensitivity, with an emphasis on their clinical implications for disease risk and the efficacy of glucocorticoid therapy in the preterm newborn.